Evaluation of Activity and Combination Strategies with the Microtubule-Targeting Drug Sagopilone in Breast Cancer Cell Lines - Eschenbrenner, Julia; Winsel, Sebastian; Hammer, Stefanie; Sommer, Anette; Mittelstaedt, Kevin; Drosch, Michael; Klar, Ulrich; Sachse, Christoph; Hannus, Michael; Seidel, Monika; Weiss, Bertram; Merz, Claudia; et al. (Frontiers in Oncology, 2011)
The molecular heterogeneity of cancer calls for individualized therapies to become the standard of care. The development of new therapeutic agents needs to include integrative translational research as early as possible. Target-specific compounds require specific diagnostic biomarker support. Tailored treatment approaches, such as specific schedules or combinations, can improve the therapeutic outcome of drugs with more general mode of action, i.e. the classical chemotherapy. Results from translational research will allow to define the optimal patient population, to tailor individual treatment and to choose treatment combinations on a rational basis. Sagopilone, a fully synthetic epothilone, is a microtubule-stabilizing agent optimized for high in vitro and in vivo activity against a broad range of tumor models, including those resistant to paclitaxel and other systemic treatments. Sagopilone development was accompanied by translational research studies to evaluate the molecular mode of action, to recognize mechanisms leading to resistance, to identify predictive response biomarkers and to establish a rationale for combination with different therapies. Here, we present an RNAi drug modifier screen interrogating 300 genes in four cancer cell lines. Defects of the spindle assembly checkpoint (SAC) were identified to cause resistance against sagopilone-induced mitotic arrest and apoptosis. Potential biomarkers for resistance are SAC-defects like mutations in the SAC-kinase BUB1B and chromosomal heterogeneity and polyploidy since they imply an increased tolerance for aberrant mitosis. The RNAi drug modifier screen identified the enhancement of sagopilone-induced mitotic arrest by inhibition of the mitotic kinesin KIF2C (MCAK) as potential combination strategy. These new findings are correlated with results from previous studies. We discuss successes and failures of our integrative preclinical development program and provide recommendations for future oncology projects.